Community evaluation of VECTRON™ T500, a broflanilide insecticide, for indoor residual spraying for malaria vector control in central Benin; a two arm non‑inferiority cluster randomised trial - Tokponnon, Filémon (My University, 2023)
VECTRON™ T500 is a wettable powder IRS formulation of brofanilide, a newly discovered insecticide. We performed a two-arm non-inferiority community randomised evaluation of VECTRON™ T500, compared to Fludora® Fusion against pyrethroid-resistant Anopheles gambiae s.l. in an area of high coverage with pyrethroid-only nets in the Za-Kpota District of central Benin. One round of IRS was applied in all consenting households in the study area. Sixteen clusters were randomised (1:1) to receive VECTRON™ T500 (100 mg/m2 for brofanilide) or Fludora® Fusion (200 mg/m2 for clothianidin and 25 mg/m2 for deltamethrin). Surveys were performed to assess adverse events and the operational feasibility and acceptability of VECTRON™ T500 among spray operators and household inhabitants. Human landing catches were conducted in 6 households every 1–2 months for up to 18 months postintervention to assess the impact on vector densities, sporozoite rates and entomological inoculation rates. Bottle bioassays were performed to monitor vector susceptibility to pyrethroids, brofanilide and clothianidin. Monthly wall cone bioassays were conducted for 24 months to assess the residual efcacy of the IRS formulations using susceptible and pyrethroid-resistant An. gambiae s.l. A total of 26,562 female mosquitoes were collected during the study, of which 40% were An. gambiae s.l., the main malaria vector in the study area. The vector population showed high intensity pyrethroid resistance but was susceptible to brofanilide (6 µg/bottle) and clothianidin (90 µg/bottle). Using a non-inferiority margin of 50%, vector density indicated by the human biting rate (bites/person/night) was non-inferior in the VECTRON™ T500 arm compared to the Fludora® Fusion arm both indoors (0.846 bites/p/n in Fludora® Fusion arm vs. 0.741 bites/p/n in VECTRON™ T500 arm, IRR 0.54, 95% CI 0.22–1.35, p= 0.150) and outdoors (0.691 bites/p/n in Fludora® Fusion arm vs. 0.590 bites/p/n in VECTRON™ T500 clusters, IRR 0.75, 95% CI 0.41–1.38, p = 0.297). Sporozoite rates and entomological inoculation rates did not difer signifcantly between study arms (sporozoite rate: 0.9% vs 1.1%, p= 0. 0.746, EIR: 0.008 vs 0.006 infective bites per person per night, p= 0.589). Cone bioassay mortality with both VECTRON™ T500 and Fludora® Fusion was 100% for 24 months post-IRS application on both
Keywords: Community evaluation; VECTRON™ T500; broflanilide; indoor residual spraying insecticide; non‑inferiority cluster randomised trial Benin